SUPPORTING BILINGUAL PRESCHOOL CHILDREN IN THE DIGITAL ENVIRONMENT - N.M. Rodina; E.Y. Protasova (Многоязычие в образовательном пространстве, 2024)
Digital technologies are increasingly being used in preschool education as a way to support learning and development. These technologies can include tablets, computers, and educational software that are designed specifically for young children. Growing up bilingual in the digital world can be a great advantage for children. Being able to speak more than one language can open up many opportunities and allow children to communicate with a wider range of people. It can also have cognitive benefits, such as improving problem-solving and multitasking skills. In the digital world, there are many resources available to help children practice and improve their language skills. For example, there are online language learning programs, educational games, and social media groups for speakers of specific languages. Children can also connect with other bilingual children and native speakers through online language exchange programs. It is important for parents to ensure that their children are using the internet safely and responsibly, regardless of their language skills. This includes setting appropriate limits on screen time, supervising their online activities, and teaching them to be cautious about sharing personal information online.